Mitigation technologies and best practices - Falco, F. de; Nikiema, Josiane; Wagner, S. (Organization for Economic Cooperation and Development, 2021)
This chapter documents and assesses available best practices and technologies that can be employed to mitigate the release of microplastics from textiles and tyres into the environment. The chapter follows a life-cycle approach, discussing options implementable at the design and manufacturing, use and end-of-life phases, as well as options for the end-of-pipe capture of microplastics.